«en Archivarpost en af de faae Belønninger, en Stat har» - Ine Fintland (Heimen)
Abstract Archival leadership and the role of the archivist during the 1800s have been studied by examining two of the leaders of the Norwegian National Archives at that time. Documents from Henrik Wergeland were chosen as he was the first in the position. Michael Birkeland's material was studied because he was in the chair for the longest period. Both of them have made important contributions theoretically and practically to the development of public archives in Norway. The findings show that the professional challenges met 170 years ago are quite similar to those faced today, even though the medium then was paper, and the hot topic today is digitally transmitted material. The core questions were: What to keep? How to get an overview over the material? How to store it? Who is going to take care of it? How to communicate the information to the users? The archival description is an important instrument for opening the archives to future users. These descriptions are written by archivists. For the purpose of source criticism, we need to know the role and competence of these authors at different times. Development of archival practice is a leadership task. This task is regrettably little studied.